2018
DOI: 10.1002/ca.23210
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical consideration of the occipital cutaneous nerves and artery for the safe treatment of occipital neuralgia

Abstract: There is no standardized approach to the greater occipital nerve (GON) block technique for treating occipital neuralgia. The aim of the present study was to validate the previously-suggested guidelines for conventional injection techniques and to provide navigational guidelines for safe GON block. The GON, lesser occipital nerve (LON) and occipital artery (OA) were carefully dissected in the occipital region of embalmed cadavers. Using a 3 D digitizer, the GON, LON, and OA were observed on the two reference li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
2
13
0
1
Order By: Relevance
“…Despite the limited distributions of the LON and TON in the lower occipital region, our study using Sihler’s staining confirmed the presence of multiple interconnections or areas of overlap among the LON, TON, and GON that had been reported previously by several gross anatomical studies. 1 , 3 , 18 Importantly, the present study clearly shows that some branches of the TON traverse horizontally and cross the GONl, whereas previous descriptions only noted that the branches ascend vertically. 19 Collectively, our anatomical findings explain the complex pain patterns that are often experienced in the occipital regions.…”
Section: Discussionsupporting
confidence: 45%
See 4 more Smart Citations
“…Despite the limited distributions of the LON and TON in the lower occipital region, our study using Sihler’s staining confirmed the presence of multiple interconnections or areas of overlap among the LON, TON, and GON that had been reported previously by several gross anatomical studies. 1 , 3 , 18 Importantly, the present study clearly shows that some branches of the TON traverse horizontally and cross the GONl, whereas previous descriptions only noted that the branches ascend vertically. 19 Collectively, our anatomical findings explain the complex pain patterns that are often experienced in the occipital regions.…”
Section: Discussionsupporting
confidence: 45%
“… 3 It serially passes or pierces the layered back muscles such as the obliquus capitis inferior (on 2.5–3 cm lateral to midline), the semispinalis capitis (on 1–1.5 cm inferior to the SNL and 3 cm lateral to midline), and the trapezius (on 1–1.5 cm inferior to the SNL and 2.5–3.5 cm lateral to midline). 1 , 16 , 17 In the past, previous studies have focused on the emergence of the nerves on the layered back muscles for guiding nerve blocks. However, the detailed distribution of the cutaneous nerve fibers should be examined for diagnosis and treatment of the nerve triggering the pain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations